Pengaruh Pemberian Pupuk Kandang terhadap Pertumbuhan Rumput Gajah (Pennisetum purpureum) pada Pemotongan Pertama - karmila, yeni; Zulkarnaini, Zulkarnaini; Utama, Bopalyon Pedi; wulan, Wulan (STOCK Peternakan, 2023)
This research aims to determine the effect of manure fertilizer application and to find the optimal manure fertilizer dose for the growth of elephant grass (Pennisetum purpureum). The study was conducted at the Experimental Garden of the Faculty of Agriculture, Muara Bungo University, in Sungai Binjai Village, Bathin III District, Bungo Regency, Jambi Province. The research was carried out from February 4, 2017, to April 4, 2017.